Benefits of physical therapy in the quality of life of mouth breathing children: Literature review - de França, Natália B. M.; Ferreira, Fátima S.; Lima, Rubens A.; Ferreira, Juliana R.; Sales, Késsia N. A. (Brazilian Journal of Health and Biomedical Sciences, 2019)
Introduction: The correct breathing process is through the nasal route, since it provides that the air during aspiration is filtered, humidified and heated, thus conditioning the lungs for gas exchange to occur. Allergic processes or other forms of affections can lead to the obstruction of the passage of air through the nose, leading the body to make an alternative adaptation for the passage of air to occur through the mouth. A person who uses the mouth to breathe is called a mouth breather. Once this adaptive process occurs, as a way to compensate for this alternative airway, the body promotes a series of alterations in several segments of the body, such as changes in the postural, respiratory, behavioral and stomatognathic systems. Several techniques are used to treat the musculoskeletal dysfunctions presented by mouth breathers. Objective: to analyze how physiotherapy can contribute to the improvement of the quality of life of mouth breathing children and to find out which are the most effective treatments. Methods: a search of data in the literature was carried out by consulting the following electronic databases: Scielo, Bireme, Pub Med, Lilacs Google Scholar, as well as specialized books in the field. We excluded articles published before the year 2000. Result: Among the analyzed articles, we perceive that the treatment of mouth breathers occurs in a multidisciplinary way, since it presents changes that encompass several body and systemic segments. Among the professionals involved in the rehabilitation process, we highlight the role of physiotherapists. Conclusion: the physiotherapist is qualified to intervene in this pathology, with expertise in evaluation and establishment of the best treatment program, with physiotherapeutic conduits, allowing an improvement in respiratory patterns. Keywords: Mouth breathing children; Physiotherapy; Postural evaluation; Treatment.